(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
The transformation of pharmaceutical markets has intensified the need for structured quality management systems in community pharmacy networks. This study investigates the impact of Good Pharmacy Practice (GPP) guidelines and ISO 9001-based quality management systems on operational efficiency, service quality, and economic performance of community pharmacies. The research is based on an empirical analysis of a pharmacy chain operating in Samarkand, Uzbekistan, during 2024–2026. The results demonstrate that systematic quality management implementation contributes to process standardization, risk reduction, improved patient trust, and sustainable financial performance. The findings highlight the strategic importance of quality management systems for pharmacy networks operating in developing pharmaceutical markets.